METODE PENELITIAN KUALITATIF DALAM BIDANG BIMBINGAN DAN KONSELING - Gumilang, Galang Surya (JURNAL FOKUS KONSELING, 2016)
This article describes and discusses the nature of qualitative research methods,the characteristics of qualitative research methods, the position of qualitativeresearch methods in guidance and counseling, qualitative research methods inguidance and counseling: reflections on Indonesia, alternative types ofqualitative research methods in guidance and counseling, data collectionmethods qualitative research in guidance and counseling, the stages ofqualitative research in guidance and counseling. Qualitative research methodscan be applied in guidance and counseling kaena forward objektifistik based onreal data in the field. Type of qualitative research papers are suitable to beapplied in the study guidance and counseling that is the type of hermeneutics,ethnography, case studies, and phenomenology because it is often used byresearchers and practitioners in the field of guidance and counseling.Key words: Qualitative research method, guidance and counseling